The Use of Cookies on Finnish Municipal Websites - Leinonen, Samuel (My University, 2024)
Privacy can be seen as a fundamental and universal human right. Therefore privacy is very important and its importance has only grown as time has passed and more and more of our lives are spent online. People generate a lot of data when they use websites on the internet and this data can be used by big companies like Google in order to better advertise to them. Municipal websites are no exception to this and they also generate a lot of data when they are used. This data can be collected through the use of analytics and marketing cookies that are on the websites. This thesis studies the use of cookies on Finnish Municipal websites by analyzing a small subset of 25 websites out of the 309 websites. The goal is the find if the websites have a proper cookie consent notice and if the cookies that they use have been categorized correctly. If they are not categorized correctly, the users will have a problem when they are giving consent to the use of cookies as the websites might use some cookies that the user unknowingly consents to. 5 out of the 25 websites are found to have problems with the cookie consent notice and 10 out of the 25 have problems with the categorization of cookies. This means that there are underlying problems with the use of cookies. The use of Google's 3rd party cookies for analytics is especially prominent. This means that many of the websites are collecting data without a clear and explicit consent from the end user although that is required by the GDPR. Also, a regular non-technical user will not be able to tell if a website is using a 3rd party service to gather data only by looking at the cookie consent notice.
Keywords: online privacy, web-based service, municipal websites, data leaks, GDPR